THE EFFECT OF HOLDING TIME ON THE QUENCHING PROCESS IN COOLING WATER CIRCULATED ON AISI STEEL 1045 - Ibrahim, Fauzi; Prasetyo, Adi; Hadi, Agung Efriyo; Ansyori, Anang (Fakultas Teknik Universitas Malahayati, 2022)
ABSTRACT Quenching is a material cooling system to obtain certain desired properties. Quenching is carried out to maintain the mechanical properties associated with the crystal structure which will be lost on slow cooling. The method used is quenching in circulating cooling water media with specimens that have been prepared in the form of AISI 1045 steel. The results obtained are the hardness of AISI 1045 steel after going through the 850oC quenching process with holding times of 30, 45, and 60 minutes, an increase of 300% from the raw material. The application of AISI 1045 steel that has been quenched shows results or hardness values that are the main raw materials for gears, crankshafts, and light vehicle spare parts. Keywords: quenching, AISI 1045 steel, circulating cooling.